The Pattern of Mindset Main Character in Home Alone Movie Directed by John Hughes: literature, movie, characters, mindset - Indryani, Indry (Media Antartika Indonesia, 2023)
This study aims to understand the intention of mindset behavior in the character Kevin in the movieThe Pattern of Mindset of Main Character. The method used in this film is a qualitative description of collectingdata requiring a lot of resources and providing an overview. The result of this study is that Kevin experiences amindset towards two types of fixed mindset and growth mindset from several factors such as parental factors,family factors and environmental factors. By concluding that Kevin's mindset in this movie is to make peopleaware that the mindset is to make life more realistic and focused in life, in every activity that is carried out, lookfor positive things and make our mindset develop. Don't be someone who is monotonous in life because of whatwe do every step of the way, not everything can be according to our expectations. Therefore develop thatmindset.